Mechanical Thrombectomy for Acute Ischemic Stroke in Nepal - Rajbhandari, Pravesh; Rajbhandari, Saujanya; Neupane, Anish (Annapurna Journal of Health Sciences, 2023)
Stroke is one of the leading causes of mortality and the number one cause of dependency in the world. Endovascular therapy has emerged as promising treatment strategy in the patient with acute ischemic stroke due to large vessel occlusion in anterior circulation. Moreover, the time window for mechanical thrombectomy have also been expanded based on the recent DAWN and DEFUSE-3 trial. It is evident that this trend could dramatically increase the number of potential patients for the treatment. Moreover, advancement in stroke imaging have guided physicians to make wisest decision in identifying suitable patient who can get benefit from the recent treatment strategies. The stroke management is evolving and continues to improve, making better outcome of the patient possible. In context of our country Nepal, it is also necessary to educate and aware medical staffs including physicians, nurses, laboratory/ radiology personnel to design a proper acute stroke team to deliver successful therapy which will eventually make a sound impact in a large number of patients with stroke. Herein, we report a case of a 69-year-old gentleman who presented with right middle cerebral artery territory infarction within 3hours of onset of symptoms and underwent mechanical thrombectomy as a part of the treatment.